Financial education affects financial knowledge and downstream behaviors - Tim Kaiser; Annamaria Lusardi; Lukas Menkhoff; Carly Urban (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
We study the rapidly growing literature on the causal effects of financial education programs in a meta-analysis of 76 randomized experiments with a total sample size of over 160,000 individuals. The evidence shows that financial education programs have, on average, positive causal treatment effects on financial knowledge and downstream financial behaviors. Treatment effects are economically meaningful in size, similar to those realized by educational interventions in other domains and are at least three times as large as the average effect documented in earlier work. These results are robust to the method used, restricting the sample to papers published in top economics journals, including only studies with adequate power, and accounting for publication selection bias in the literature. We conclude with a discussion of the cost-effectiveness of financial education interventions.
Keywords: D14; G53; I21; 330; financial education; financial literacy; financial behavior; RCT; metaanalysis